The Effect of Profitability on Corporate Income Tax Payable on Food And Beverage Companies Listed on The Indonesian Stock Exchange - Kartika, Tita; Nurochman, Maman; Apriandi, Devy Widya; Rahmawati, Yuni (Jurnal Ekuisci, 2024)
The title of this research is the Effect of Profitability on Corporate Income Tax Payable on Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2016-2020 period. This study aims to identify the effect of profitability as measured by the ratio of net profit margin (NPM) to corporate income tax payable. The population used is nine food and beverage companies listed on the Indonesia Stock Exchange for 2016-2020. The method used in this study is quantitative. The type of data used is secondary data obtained from each company's financial statements on the official website of the Indonesia Stock Exchange (www.IDX.co.id). The sampling technique used was purposive sampling. The data analysis method was carried out with the help of the IBM SPSS version 25 program using the classical assumption test, simple linear regression analysis, and hypothesis testing. The results of this study indicate that profitability (NPM) does not significantly affect corporate income tax